PENGEMBANGAN PETA DIGITAL BERBANTUAN KOMPUTER BAGI MAHASISWA UAD PADA MATA KULIAH MATERI PEMBELAJARAN IPS - Dholina Inang Pambudi (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
Research and development objectives are to: (1) Produce a map ditigal computer-aided development for students in courses Learning Materials Social Sciences (IPS) on student PGSD particularly mineral and mining of natural resources in the DIY (2). Determine the feasibility of products developed from the aspect of materials and media, as well as aspects of the student. This research is the subject of research and development consists of one expert material, one media expert, the trial is limited to half of the students PGSD UAD 3. Data collection instrument in the form of sheet material validation to experts and media experts, questionnaire for students. The acquired data is processed and analyzed using descriptive statistics as the material for the revision of the product to be eligible to use for testing in the field so that later can be used as a viable media used for students who follow courses Learning Materials IPS particularly mineral and mining of natural resources in DIY.Hasil of This is a research and development; computer-aided digital map media considered feasible to use as a tool in the learning process based on the assessment of expert judgment matter experts, media experts, and limited testing at PGSD students FKIP UAD. Based on the assessment criteria of material experts are included in the category of "very good" with a final value of 81, the assessment criteria of media experts are included in the category of "good" with a final value of 80, while the criteria for assessment of students in a limited trial obtained the amount of the final value in terms of aspects Preliminary 81, aspects of learning 76, the quality aspects of redaction 76, aspects of the illustrations 79, aspect of packaging 79, the graphic aspect 79, the aspect of voice, video, navigation 75, aspects of the efficiency of program 79, all the "good" category, and the last aspect of expediency media for 88 student category of "very good". Overall indicates that the digital map computer aided for students UAD in the course of learning materials IPS fit for use as a medium that is appropriate for students to explain the material, especially natural resources and mineral mines in the province so that prospective primary school teachers will have enough stock to hang to learners in school.